1985
DOI: 10.1113/jphysiol.1985.sp015826
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic responses evoked in muscles of the forelimb by intracortical stimulation in the cat.

Abstract: SUMMARY1. Chronically implanted microwires were used to deliver brief trains of electrical stimuli (11 cathodal pulses at 330 Hz and intensity 5-35,A) to sixty-two locations in the grey matter of the pericruciate cortex in cats.2. Electromyographic (e.m.g.) responses in the contralateral forelimb were recorded from a total of ten muscles (four to eight in each animal) acting about the shoulder, elbow and wrist and on the digits. The animals were relaxed with little background e.m.g. in the muscles and as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…This relationship makes it possible to infer the forelimb joint that an individual PTN influences from the somatosensory receptive field that it has. Indeed, although axons of individual PTN from the forelimb representation of the motor cortex give off several branches along cervical and thoracic segments of the spinal cord most often synapsing upon interneurons of laminae IV-VII (Chamber and Liu 1957; Shinoda et al 1986), and there is a rich spinal interneuron network that mediates signals from PTNs to motoneurons, earlier reports have shown that microstimulation in the forelimb region of the motor cortex typically produces contraction in single muscles or in small groups of muscles in the area that composes the receptive field at the stimulation site (Armstrong and Drew 1985a;Asanuma et al 1968;Murphy et al 1975;Rosen and Asanuma 1972;Sakata and Miyamoto 1968) and affects monosynaptic reflexes of only one or two muscles (Asanuma and Sakata 1967). Even when series of pulses of 20 A were used in locomoting subjects, microstimulation of a quarter of sites within forelimb motor cortex still affected only one or two muscles (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This relationship makes it possible to infer the forelimb joint that an individual PTN influences from the somatosensory receptive field that it has. Indeed, although axons of individual PTN from the forelimb representation of the motor cortex give off several branches along cervical and thoracic segments of the spinal cord most often synapsing upon interneurons of laminae IV-VII (Chamber and Liu 1957; Shinoda et al 1986), and there is a rich spinal interneuron network that mediates signals from PTNs to motoneurons, earlier reports have shown that microstimulation in the forelimb region of the motor cortex typically produces contraction in single muscles or in small groups of muscles in the area that composes the receptive field at the stimulation site (Armstrong and Drew 1985a;Asanuma et al 1968;Murphy et al 1975;Rosen and Asanuma 1972;Sakata and Miyamoto 1968) and affects monosynaptic reflexes of only one or two muscles (Asanuma and Sakata 1967). Even when series of pulses of 20 A were used in locomoting subjects, microstimulation of a quarter of sites within forelimb motor cortex still affected only one or two muscles (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…We took advantage of the fact that in the spinal cord most PTNs influence the same part of the limb that they receive somatosensory information from (Asanuma et al 1968;Murphy et al 1975;Rosen and Asanuma 1972;Sakata and Miyamoto 1968). Moreover, even though axons of individual PTNs from the forelimb representation of the motor cortex branch along several cervical and thoracic segments of the spinal cord (Shinoda et al 1986), physiological experiments have shown that microstimulation in about half of sites within the forelimb motor cortex at 15 A produces effects in only one or two muscles (Armstrong and Drew 1985a). Spike-triggered averaging of EMGs in primates showed that about half of PTNs influence motoneuron pools that innervate muscles working around a single joint of the limb (Buys et al 1986;McKiernan et al 1998).…”
mentioning
confidence: 97%
“…In brief, the area immediately adjacent to and inside the lateral one-half of the cruciate sulcus in the cat is considered to be the motor cortex. This is based on a considerable body of data obtained by means of inactivation, stimulation, and recording techniques (Armstrong and Drew 1985;Beloozerova and Sirota 1993a;Drew 1993;Nieoullon and Rispal-Padel 1976;Vicario et al 1983), as well as on histological considerations (Ghosh 1997;Myasnikov et al 1997). Microelectrode entry points on the cortical surface are schematically shown (see Fig.…”
Section: Identification Of Cortical Motor Areamentioning
confidence: 99%
“…We made penetrations within the lateral portion of area 4␥ (Ghosh 1997;Hassler and Muhs-Clement 1964), a zone extending from about 2 mm caudal, 5 mm rostral, and 2 mm lateral to the cruciate sulcus. This is the forelimb representation (Armstrong and Drew 1985;Chakrabarty and Martin 2000;Keller 1993;Pappas and Strick 1981) and it projects densely to the cervical enlargement in kittens and adult cats (Ghosh 1997;Li and Martin 2000;Martin 1996). To ensure that we thoroughly explored the forelimb zone, in all experiments we examined the region until we encountered a consistent band of ineffective sites or nonforelimb sites, indicating the limits of excitable forelimb motor cortex.…”
Section: Icms Protocolmentioning
confidence: 99%